Improving health-related quality of life in single-sided deafness: a systematic review and meta-analysis - Kitterick, Pádraig T.; Lucas, Laura; Smith, Sandra N. (Karger, 2016)
Unilateral severe-to-profound hearing loss, or single-sided deafness (SSD), impairs listening abilities supported by the use of two ears, including speech perception in background noise and sound localisation. Hearing-assistive devices can aid listening by re-routing sounds from the impaired to the non-impaired ear or by restoring input to the impaired ear. A systematic review of the literature examined the impact of hearing-assistive devices on the health-related quality of life (HRQoL) of adults with SSD as measured using generic and disease-specific instruments. A majority of studies used observational designs, and the quality of the evidence was low to moderate. Only two studies used generic instruments. A mixed-effect meta-analysis of disease-specific measures suggested that hearing-assistive devices have a small-to-medium impact on HRQoL. The Speech, Spatial and Qualities of Hearing Scale and the Health Utilities Index Mark 3 (HUI3) were identified as instruments that are sensitive to device-related changes in disease-specific and generic HRQoL, respectively.